Mechanism of plant immune activation and signaling: Insight from the first solved plant resistosome structure. Issue 8 (22nd May 2019) - Feng, Baomin; Tang, Dingzhong
Abstract : This commentary introduces an exciting breakthrough: the first solved structure of a plant NLR immune receptor complex. The significance of this work, including the similarity between the activation of NLRs from plants and animals, and potentially novel mechanism of immune signaling in plants, were discussed and put into perspective.